Joe T. Patterson and the White south's dilemma : evolving resistance to Black advancement - Luckett, Robert E., Jr (University Press of Mississippi, 2015)
As Mississippi's attorney general from 1956 to 1969, Joe T. Patterson led the legal defense for Jim Crow in the state. He faced a dilemma that confronted all white southerners: how to maintain an artificially elevated position for whites in southern society without resorting to violence or intimidation.